ANALISIS PENGARUH PROMOSI, INOVASI PRODUK DAN CITRA PERUSAHAAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI PERCEIVED VALUE (STUDI KASUS PADA MILENIAL YANG MENGGUNAKAN MASKAPAI GARUDA INDONESIA) - Melisa, Pricilia; L. Mandey, Silvya; Hasan Jan, Arrazi (FEB Universitas Sam Ratulangi Manado, 2020)
This research aims to determine the effect of Promotion, Product Innovation and Corporate Image on Purchase Decision through Perceived Value in a case study on millennials using the Garuda Indonesia airline. The sampling method used was probability sampling with certain criteria. The data collection technique used was by distributing questionnaires to 216 respondents aged 19-39 years who had used Garuda Indonesia at least 1-2 times. The data collected was then analyzed using path analysis using the SPSS 20 program. The results of this study indicate that Promotion, Product Innovation and Corporate Image have a significant effect on Perceived Value. Promotion has a significant direct and indirect effect on Purchase Decisions, while product Innovation and Corporate Image have a direct but insignificant effect on Purchase Decisions and indirectly have a significant effect on Purchase Decisions through Perceived Value. Perceived Value has a significant effect on Purchase Decisions for millennials using the Garuda Indonesia airline